Ruptured Abdominal Aortic Aneurysm : The Definitive Manual - Starnes, Benjamin W.; Mehta, Manish; Veith, Frank J. (Springer International Publishing : Imprint: Springer, 2017)
This manual is designed to serve as the standard for the management of patients with ruptured abdominal aortic aneurysm (AAA) by means of modern techniques. All aspects are covered, from pathogenesis, clinical presentation, and diagnosis through to initial management, operative strategies, postoperative complications, outcomes, and quality of life issues. The book is based on the experience gained at a leading U.S. institution (Harborview Medical Center, University of Washington) that treats up to 40 patients with ruptured AAA annually and is highly respected for its expertise in this medical emergency. The team at Harborview Medical Center has recently shown that the implementation of a structured protocol for the management of ruptured AAA, with emphasis on an "endovascular-first" strategy, dramatically reduces mortality and complications. This has led to a sea change in the way in which patients are managed. There is an increasing hunger for information on these codified protocols, and Ruptured Abdominal Aortic Aneurysm: The Definitive Manual will be invaluable for both surgeons and critical care physicians.- Resumé vydavatel